PAKET WISATA TRADISI SELAMATAN JAWAMELAYU DESA SELATBARU KABUPATEN BENGKALIS - Desnita Windi Asnani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Javanese Malay tradition is a one cultural and relogious potential that is like being introduced to tourist who will do tourism activities to Selatbaru Village Bengkalis Districts. This research aims to knows make about tour package Javanese Malay tradition Selatbaru Village Bengkalis Districts. This research using qualitative methods with a descriptive approach. The research subject was the village head, public figure Selatbaru Village, sub-district head, and society Selatbaru Village. Data collection is done by library research, observation, interview, and documentation. While data analysis is done by collecting data, data education, data presentation, and conclusion. From the research that has been done, it can be concluded that Selatbaru Village is a tourism destination that offers a wealth of cultural heritage. From that, formed a tour package explored cultural heritage in Selatbaru Vlillage for a day at a cost Rp. 216.000/person and this package also offers tour packages staying for 2 days 1 night at a cost Rp. 513.000/ person. Keyword : Tour Package, Selatbaru Village.